Digital Literacy Using Twitter for Learning English Vocabulary and Grammatical - Melliyani Melliyani; Mardiyati mardiyati (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this article is to examine the usage of Twitter in the study of English vocabulary and grammar." Which is to say, digital literacy is extensively employed nowadays. Students learn about digital literacy using digital media, searching for, identifying, analyzing, and using information. This article discusses the subject of Twitter usage, a survey in which 25 respondents who used Twitter participated. The writers aided in the production of this paper using qualitative research. Twitter users use Twitter to improve their English vocabulary and grammar by searching for Tweets from other Twitter users across the world and recognizing which Tweets originate in countries where English is the predominant language.